Building trust through knowledge sharing: Implications for incentive system design - Haesebrouck, Katlijn; Van den Abbeele, Alexandra; Williamson, Michael G. (Accounting, Organizations and Society, 2021)
We examine whether knowledge sharing can enhance the efficacy of implicit, trust-based incentives. Using a stark laboratory experiment, we find support for theory suggesting that individuals believe that their knowledge is an important part of their identity, making it costly to share, but facilitating greater trust that recipients of this knowledge will reciprocate with future rewards. Utilizing participants with substantial work experience, results from additional scenario-based experiments demonstrate practical implications of this theory. Collectively, the results from our experiments show that individuals help others less when the help conveys personal knowledge relative to when it does not absent the prospect of rewards, but more when they can expect future rewards (i.e., with implicit incentives). Importantly, knowledge sharing increases the efficacy of implicit incentives more when they are determined by the help recipient relative to someone else (e.g., a supervisor). Collectively, we contribute to a better understanding of incentive systems designed to promote knowledge sharing in practice.